Pomirki, Kamarka, Pietrus, Radiów – o etymologii ludowej i naukowej wybranych mikrotoponimów z obszaru dawnej Łemkowszczyzny - Słabczyński, Robert (Stylistyka, 2024)
The purpose of the article is to present the folk etymology of selected microtoponyms, their scientific verification aimed at establishing the actual origin of the names, showing differences between the folk and scientific etymology. The article also describes the mechanisms governing folk etymological reinterpretation in the ethnolinguistic borderlands. This is because the villages covered by the study are located in areas that until the 1940s had been inhabited mainly by Lemkos, the population of Polish origin being a minority. It was found that most often etymological reinterpretation concerned mainly names with topographical and affiliation motivation, which was due to changes in the population structure after the displacement of Lemkos, as well as significant transformations in the topographical space of the study area.